2020
DOI: 10.1002/cctc.202001480
|View full text |Cite
|
Sign up to set email alerts
|

Role of Recrystallization in Alkaline Treatment on the Catalytic Activity of 1‐Butene Epoxidation

Abstract: Two alkylol amines, which were ethanolamine (EOA) and triethanolamine (TEOA), were used to posttreat nanosized titanium silicalite‐1 (TS‐1) to improve its catalytic activity for 1‐butene epoxidation. Comparative studies were conducted to clarify the influences of the EOA and TEOA concentrations on the physicochemical properties through detailed characterization. EOA treatment can dissolve the framework Si, [SiO4], on the external surface of TS‐1, generating some macropores. TEOA serves as structure‐directing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The conversion, selectivity, and space time yield were calculated through the formula below. 27,37,39,40 Conversion % Moreover, the sample failed to crystalize via direct synthesis due to the high content of heteroatoms, even up to 20 days, in line with the conclusion reported in the literature that high content metals inhibit nucleation. 13,41,42 The XRD patterns (Fig.…”
Section: Catalytic Reactionssupporting
confidence: 88%
See 2 more Smart Citations
“…The conversion, selectivity, and space time yield were calculated through the formula below. 27,37,39,40 Conversion % Moreover, the sample failed to crystalize via direct synthesis due to the high content of heteroatoms, even up to 20 days, in line with the conclusion reported in the literature that high content metals inhibit nucleation. 13,41,42 The XRD patterns (Fig.…”
Section: Catalytic Reactionssupporting
confidence: 88%
“…The conversion, selectivity, and space time yield were calculated through the formula below. 27,37,39,40 Space time yield (g g cat −1 h −1 ) = conversion × selectivity × WHSV…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct epoxidation of propene to propene oxide has achieved successful industrial implementations under mild reaction conditions . However, even if ethene and 1-butene epoxidation has attended recent research interest, most of the previous research has aimed to compare different catalysts more than to investigate how the epoxidation reaction and side reactions are affected by the different process parameters. The studies have in most cases been limited to the use of batch reactor technology or fixed beds operating under stationary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature reports studies on catalyst modifications, solvent effects, , and reactor configurations for propene epoxidation, while for butenes, most of the previous investigations have been devoted to catalyst modifications applied in batch reactors without any detailed studies on the product selectivity and reactant conversion. Nevertheless, the studies carried out in continuous mode for 1-butene epoxidation are reported over 10 h of reaction displaying a constant decrease in the catalyst activity with time-on-stream in each catalyst tested, evidently due to the reactant and product capture on the catalyst surface. , Therefore, it is important to study these two reaction systems in a broad set of conditions to understand if isomers have similar reaction mechanisms and catalyst activities. On the other hand, it is necessary to work in a continuous regime due to the changes reported for 1-butene between 10 and 350 h. , Isobutene epoxidation has not been reported extensively; the study of the epoxidation of isobutene has been reported once to compare the rate with other olefins without any deeper analysis of the byproducts.…”
Section: Introductionmentioning
confidence: 99%